What can we learn from commercial insecticides? Efficacy, toxicity, environmental impacts, and future developments - Rezende-Teixeira, Paula; Dusi, Renata G.; Jimenez, Paula C.; Espindola, Laila S.; Costa-Lotufo, Letícia V. (Environmental pollution (1987), 2022)
Worldwide pesticide usage was estimated in up to 3.5 million tons in 2020. The number of approved products varies among different countries, however, in Brazil, there are nearly 5000 of such products available. Among them, insecticides correspond to a group of mounting importance for controlling crop pests and disease-associated vectors in public health. Unfortunately, resistance to commercially approved insecticides is commonly observed, limiting the use of these products. Thus, the search for more effective and environmentally friendly products is both a challenge and a necessity since several insecticides are no longer allowed in many countries. In this review, we discuss the historical strategies used in the development of modern insecticides, including chemical structure alterations, mechanism of action and their impact on insecticidal activity. The environmental impact of each pesticide class is also discussed, with persistence data and activity on non-target organisms, along with the human toxicological effect. By tracing the historical route of discovery and development of blockbuster pesticides like DDT, pyrethroids and organophosphates, we also aim to categorize and relate the successful chemical alterations and novel pesticide development strategies that resulted in safer alternatives. A brief discussion on the Brazilian registration procedure and a perspective of insecticides currently approved in the country was also included. [Display omitted] •Chronology of discovery and development of pesticides from DTT to biopesticides.•Target and MoA are important means for categorization of modern insecticides.•Research on environmentally friendly biopesticides should be globally stimulated.•In Brazil, approval of new pesticides increased by 600% between 2001 and 2021.